2013
DOI: 10.1007/s00253-013-5388-6
|View full text |Cite
|
Sign up to set email alerts
|

Pectin-modifying enzymes and pectin-derived materials: applications and impacts

Abstract: Pectins are complex branched polysaccharides present in primary cell walls. As a distinctive feature, they contain high amount of partly methyl-esterified galacturonic acid and low amount of rhamnose and carry arabinose and galactose as major neutral sugars. Due to their structural complexity, they are modifiable by many different enzymes, including hydrolases, lyases, and esterases. Their peculiar structure is the origin of their physicochemical properties. Among others, their remarkable gelling properties ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 177 publications
2
74
1
1
Order By: Relevance
“…It could therefore be assumed that the presence of acetylated galacturonic acid residues in the hairy regions of guava pectins and the swapping of the rhamnose/galacturonic acid units explain, as suggested by [26], their resistance to a harsh enzyme treatment. The importance of rhamnogalacturonan hydrolases and of rhamnogalacturonanacetylesterases is well documented [29]. Although we did not detect these enzyme activities in Klerzyme Extra, the highly acetylated residual fraction in the serum might indicate that the enzymes may not be active on these substrates.…”
contrasting
confidence: 61%
“…It could therefore be assumed that the presence of acetylated galacturonic acid residues in the hairy regions of guava pectins and the swapping of the rhamnose/galacturonic acid units explain, as suggested by [26], their resistance to a harsh enzyme treatment. The importance of rhamnogalacturonan hydrolases and of rhamnogalacturonanacetylesterases is well documented [29]. Although we did not detect these enzyme activities in Klerzyme Extra, the highly acetylated residual fraction in the serum might indicate that the enzymes may not be active on these substrates.…”
contrasting
confidence: 61%
“…They are present as the major components of middle lamella between the cells in the form of calcium pectate and magnesium pectate (Bonnin et al 2014). Pectic polysaccharides exist in the cell wall as either ''smooth region'' of linear copolymer a (1-4)-linked GalUA (galacturonic acid) or ''hairy region'' that have attached a (1-2)-linked rhamnosyl residues that may be substituted with Ara (arabinan)-and Gal (galactan)-rich side chains (Caffall and Mohnen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, a significant initial activity of PME make available the substrate for PG (PINTO et al, 2011). In this line, Bonnin et al (2014) reported that PME promotes partial demethylation of methyl esters from polygalacturonic and pectic acids, promoting depolymerization and solubilization of pectic compounds by PG.…”
Section: Firmnessmentioning
confidence: 95%
“…This variable showed a significant quadratic behavior and decline in value, followed by an increase, as observed in Table 4. his initial fall in TA could be explained by an increasing consumption of organic acids during respiratory process, being converted into simple sugars (OLIVEIRA JUNIOR et al, 2006;CHITARRA;CHITARRA, 2005). The later increase in TA may be associated with the formation of galacturonic acid from pectin hydrolysis by PME and PG (BONNIN et al, 2014;PINTO et al, 2011). The metabolic activity increase at climacteric peak could have contributed to the synthesis of organic acids (PAULL;CHEN, 1983).…”
Section: Tamentioning
confidence: 99%
See 1 more Smart Citation